ANALISIS KESESUAIAN FASILITAS PRAKTIKUM TEKNIK PENGELASAN TERHADAP STANDAR KOMPETENSI DI SMK NEGERI 1 GUGUK - Jimi Afrinaldi; Junil Adri; Arwizet K.; Andril Arafat (Unversitas Negeri Padang, 2024)
In the midst of the Industrial 4.0 era, there is an escalating demand for competent and highly skilled labor in the manufacturing and construction sectors, making this need increasingly urgent. Welding technology, as a crucial expertise in these fields, necessitates high-quality vocational education to produce competent labor. SMK Negeri 1 Guguk focuses on providing welding engineering education in accordance with industry standards. This study aims to analyze the adequacy of the welding engineering practicum facilities at SMKN 1 Guguk with prevailing competency standards. The method employed is a mixed-method approach combining qualitative and quantitative techniques, including surveys, interviews, documentation, and observations. The results indicate that while certain aspects of the practicum facilities, such as educational media and equipment, comply with the standards outlined in Permendikbud Number 34 of 2018, there are significant deficiencies in the infrastructure, facilities, furniture, and practical tools. The identified challenges include budget constraints, lack of equipment maintenance, and inadequacies in providing the latest technology. This study recommends enhancing practicum facilities, integrating the latest technologies, and improving equipment maintenance methods. These recommendations are anticipated to support the development of student competencies and enhance their readiness for the global labor market. Furthermore, the findings of this study are expected to impact vocational education broadly and contribute to the literature in the field of welding engineering vocational education, thereby creating a more prepared and highly competitive workforce.